Chronic Exposure to Alcohol Inhibits New Myelin Generation in Adult Mouse Brain - Guo, Feng; Zhang, Yi-Fan; Liu, Kun; Huang, Xu; Li, Rui-Xue; Wang, Shu-Yue; Wang, Fei; Xiao, Lan; Mei, Feng; Li, Tao (Frontiers in Cellular Neuroscience, 2021)
Chronic alcohol consumption causes cognitive impairments accompanying with white matter atrophy. Recent evidence has shown that myelin dynamics remain active and are important for brain functions in adulthood. For example, new myelin generation is required for learning and memory functions. However, it remains undetermined whether alcohol exposure can alter myelin dynamics in adulthood. In this study, we examine the effect of chronic alcohol exposure on myelin dynamics by using genetic approaches to label newly generated myelin (NG2-CreERt; mT/mG). Our results indicated that alcohol exposure (either 5% or 10% in drinking water) for 3 weeks remarkably reduced mGFP+/NG2- new myelin and mGFP+/CC1+ new oligodendrocytes in the prefrontal cortex and corpus callosum of 6-month-old NG2-CreERt; mT/mG mice as compared to controls without changing the mGFP+/NG2+ oligodendrocyte precursor cells (OPCs) density, suggesting that alcohol exposure may inhibit oligodendrocyte differentiation. In support with these findings, the alcohol exposure did not significantly alter apoptotic cell number or overall MBP expression in the brains. Further, the alcohol exposure decreased the histone deacetylase1 (HDAC1) expression in NG2 positive OPCs, implying epigenetic mechanisms were involved in the arrested OPC differentiation. Together, our results indicate that chronic exposure to alcohol can inhibit myelinogenesis in the adult mouse brain and that may contribute to alcohol-related cognitive impairments.